Shear Design of High Strength Concrete Beams in MRFs - Campione, Giuseppe; Cucchiara, Calogero; Monaco, Alessia (Frontiers in Built Environment, 2019)
This paper presents the criteria for the shear design of high strength concrete (HSC) beams in moment resisting frames (MRFs). The formulation of an analytical model is provided for the case of beams with longitudinal reinforcement in the presence of transverse stirrups. The model is of additive type, in the meaning that the shear resistance of the beam is evaluated as the sum of several contributions. In particular, the contribution of concrete, longitudinal rebars and transversal reinforcement are taken into account. Furthermore, for assessing the concrete contribution, a classical approach is followed, according to which two effects arise in the shear mechanism: the arc and the beam effect. The features of these two resisting mechanisms are particularized to the case of HSC in steel reinforced beams and the maximum concrete contribution is limited to the maximum compressive strength of the concrete strut in biaxial state of stress. Moreover, for the evaluation of the resistance contribution of the longitudinal steel rebars in tension, the model takes into account the residual bond adherence between HSC and steel reinforcement and the spacing between subsequent cracks. The results are compared with the prescriptions currently provided in the main building codes and with different analytical models existing in the literature. For the comparison, the analytical expressions are applied to a set of experimental data available in the literature and design observations are made on the geometrical percentage of steel bars, the resistance of materials, the residual bond stress and the depth-to-shear span ratio.